Malaysia-ACute CORonary syndromes Descriptive study (ACCORD): evaluation of compliance with existing guidelines in patients with acute coronary syndrome - Ahmad, W.A.; Ramesh, S.V.; Zambahari, R. (Singapore Medical Assn., 2011)
Introduction: The ACute CORonary syndromes Descriptive study (ACCORD) is a prospective observational study that evaluates the management of acute coronary syndrome (ACS) in clinical practice and the use of antiplatelet agents in acute settings and after discharge. The secondary objective of this study was to obtain information on risk factors in a large cohort of patients with ACS.